Performance of Front Line Demonstrations on Mustard Hybrids - Singh, Atar; Singh, A. K.; Singh , Lakhan (Indian Journal of Extension Education, 2013)
Frontline demonstrations were conducted during rabi of 2011-12 at 6 Krishi Vigyan Kendras (KVKs) of Uttar Pradesh and  Uttarakhand, to study the effect of different hybrids/composites on yield and economic return parameters of mustard  (Brasica juncea) as compared to local check. It is one crop which has found place in existing cropping systems in order to  improve land use efficiency and economic gains while minimizing the risk to the farmers. Average yield (20.59 q/ha) of  mustard was obtained which was 38.18 per cent higher over local check. The net return of ` 40,820/ha was realized by the  farmers with benefit cost ratio of 2.6:1. The variety NRCDR 2 in district Sant Ravidas Nagar provided higher yield of  30.05 q/ha followed by Haridwar district (24.83q/ha) and Kaushambi district (20.90 q/ha) as compared to farmers'  practices. Variety NRCHB 506 gave average yield of 22.5 q/ha at KVK Pratapgarh and variety NRCHB 101 resulted yield  of 19.0 q/ha at KVK Saharanpur. The average yield increased ranging between 30-40 per cent over local check.
Keywords: Front line demonstrations mustard hybrids; mustard composites productivity; profitability